A Meta-Analysis on the Efficacy and Safety of Bacterial Lysates in Chronic Obstructive Pulmonary Disease - Huang, Yongkang; Pei, Yongjian; Qian, Yajuan; Yao, Zhen; Chen, Chen; Du, Juan; Shi, Minhua; Zhou, Tong (Frontiers in Medicine, 2022)
Background: chronic obstructive pulmonary disease is a common and frequently encountered disease of respiratory apparatus, and is vulnerable to infection. Increasing studies reveal that bacterial lysates play an encouraging role in preventing exacerbations in these patients. We here investigated the efficacy and safety of bacterial lysates in chronic obstructive pulmonary disease. Methods: We performed systematic research on PubMed, Embase, the Cochrane Library (central), and web of science by using the keywords and their synonyms. Two researchers screened the works of literature independently according to the inclusion and exclusion criteria, and extract data from the included studies. Another two researchers assessed the risk of bias of each included using the Cochrane risk-of-bias tool. Meta-analysis was conducted by using R (V 4.1.1, The R Foundation for Statistical Computing) and Review Manager (V 5.4.0, The Cochrane Collaboration). Results: Twenteen studies were included in this meta-analysis and the pooled results showed that bacterial lysates was effective to reduce exacerbation rate (overall: RR = 0.83, 95% CI 0.72 to 0.96; alkaline bacterial lysates subgroup [OM-85]: RR = 0.87, 95% CI 0.77 to 0.98; mechanical bacterial lysates subgroup [Ismigen]: RR = 0.70, 95% CI 0.41 to 1.20) and mean number of exacerbations (overall: SMD = -0.66, 95% CI -1.28 to -0.05; alkaline bacterial lysates subgroup [OM-85]: SMD = -1.07, 95% CI -1.69 to -0.44; mechanical bacterial lysates subgroup [Ismigen]: SMD = -0.02, 95% CI -0.23 to -0.20). Bacterial lysates were also found beneficial in allievating symputoms. The side effects were acceptable and slight. Conclusion: Bacterial lysates could be beneficial for chronic obstructive pulmonary disease patients in reducing exacerbations and alleviating symptoms. And OM-85 could be preferable based on existing evidence. Further studies were needed to validate the findings.